Economic theories of peace and war - Coulomb, Fanny, 1972- (Studies in defence economics (Chur, Switzerland), 2004)
War often comes down to one thing: money. The role of economics in the study of both peace and war is arguably then the most important single factor when it comes to the study of defence. This excellent new book from Fanny Coulomb will be of interest not only to those involved in the burgeoning field of defence economics - it will also be of vital interest to students and academics from international relations, defence studies, philosophy and political science backgrounds.